Developing illustrated story books to improve beginning reading skills and learning motivation - Felix Baskara Bhakti Utomo (Jurnal Prima Edukasia, 2018)
This research aimed (1) to produce a suitable illustrated story book in improving the students' reading skill and learning motivation, and 2) to know the effectiveness of the illustrated story book media for the beginning reading skills and learning motivation of the first grade students of SD Negeri Timbulharjo Sewon Bantul. The research method used was research and development (RD) which referred to the 10 steps developed by Borg and Gall (1983) and the determination of the number of subjects refers to the opinion of Dick and Carey (2005). The subjects of the try out were the first grade students of SD Negeri Timbulharjo 1 Sewon Bantul. The data were collected by using interview, observation, scale, performance test and worksheet. The techniques of analyzing data employed on this research were need analysis, the feasibility study media, and analysis of effectiveness of media. Normality test used using Shapiro-Wilk because data less than 50. The result of the research was (1) a set of illustrated story book media that fulfilled the feasibility based on validation by a material expert and a media expert, and teachers’ and students’ response which was in very good category; (2) the developed illustrated books media were effective to improve the beginning reading skills and students’ learning motivation. Beginning reading skills and students’ learning motivation increased significantly based on paired t-test with probability score (p) 0.05.